Structural and functional alterations in the contralateral hemisphere following pediatric intracranial surgery: a pilot longitudinal neuroimaging study - Yan, Na; Hu, Bohan; Zhai, Huina; Han, Xu; Hu, Cuiling; Guan, Xueyi; Gong, Jian (Frontiers in Human Neuroscience, 2025)
BackgroundIntracranial space-occupying lesions (ISOLs) are common pediatric conditions. Recent therapeutic advances have significantly improved survival rates, necessitating increased attention to post-operative cognitive outcomes, which are crucial determinants of patients’ quality of life.ObjectiveWhile previous studies have predominantly focused on short-term post-operative changes, this study aimed to investigate longitudinal changes in cognition, brain structure, and function of the contralateral hemisphere following pediatric neurosurgery.MethodsNineteen pediatric patients with ISOLs were enrolled in a paired design study. Cognitive assessments, structural imaging, and functional imaging data were collected at three time points: pre-operation, first post-operative follow-up (mean 75 days pre-operation), and second post-operative follow-up (mean 316 days pre-operation). Relevant metrics were computed and compared across time points.ResultsThe majority of cognitive domains exhibited a gradual longitudinal improvement trajectory, with three domains showing significant enhancement at the second follow-up compared to preoperative baseline: cognitive flexibility (t = 4.201, p = 0.001), executive function (t = 3.478, p = 0.003), and social accuracy (t = 3.248, p = 0.004). The contralesional hemisphere demonstrated alterations primarily characterized by gray matter density reduction, progressing from subcortical structures (first follow-up: thalamus, peak intensity = −7.54, cluster p < 0.016) to cortical regions (second follow-up compared to previous follow-up: superior frontal gyrus, peak intensity = −7.80, cluster p < 0.016), followed by a subsequent increase in brain activity power of smaller magnitude (second follow-up: medial superior frontal gyrus, amplitude of low frequency fluctuation, peak intensity = 5.96, cluster p < 0.016). Correlation analysis suggests that there is an association between changes in brain structure and alterations in cognitive function (r = −0.53, p = 0.019).ConclusionOur findings suggest that post-craniotomy structural and functional brain changes in children follow a subcortical-to-cortical trajectory, with structural alterations (decreased gray matter density) preceding functional activation. This process demonstrates progressive and cumulative characteristics. These modifications appear to correlate with cognitive function recovery and may represent potential mechanisms underlying spontaneous cognitive rehabilitation in pediatric patients post-surgery. Cautiously interpreted, the deeper neuroplastic mechanisms underlying these changes might involve synaptic pruning-like processes induced by external perturbation.